The human heart proteome: Two-dimensional maps using narrow-range immobilised pH gradients. - Westbrook, J; Wheeler, J; Wait, R; Welson, S; Dunn, M (2006)
The analysis of complex proteomes is undertaken using a variety of techniques and technologies such as 2-DE, surface-enhanced laser desorption ionisation, and various types of MS. In order to overcome the complexities of protein expression in discrete proteomes, sample fractionation has become an important aspect of proteomic experiments. The use of narrow-range IPGs (nrIPGs) is of special importance using the 2-DE proteomics workflow, since an enhanced visualisation of a given proteome is achieved through an improved physical separation and resolution of proteins. The work described in this paper presents a series of protein maps of the human heart left ventricle proteome that have been generated using nrIPGs for the first, IEF, dimension of 2-DE. A total of 374 gel spots were excised from seven different pH gradients, covering the range pH 3-10, giving rise to a total of 388 identifications from 110 unique proteins. Using Gene Ontologies (GOs), the identified proteins were found to be associated with 97 types of GO Process, 144 types of GO Function, and 54 types of GO Component. It is hoped that the maps presented in this paper will be of use to other researchers for reference purposes.